2018
DOI: 10.1017/jfm.2018.95
|View full text |Cite
|
Sign up to set email alerts
|

Inertial focusing of finite-size particles in microchannels

Abstract: At finite Reynolds numbers, Re, particles migrate across laminar flow streamlines to their equilibrium positions in microchannels. This migration is attributed to a lift force, and the balance between this lift and gravity determines the location of particles in channels. Here we demonstrate that velocity of finite-size particles located near a channel wall differs significantly from that of an undisturbed flow, and that their equilibrium position depends on this, referred to as slip velocity, difference. We t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 49 publications
5
66
0
Order By: Relevance
“…In the no-slip channel ( Fig. 7(a)), the migration velocity curve is similar to reported earlier for smaller particles [23]. The flow in the channel is symmetric, leading to focusing of particles at two symmetric equilibrium positions.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In the no-slip channel ( Fig. 7(a)), the migration velocity curve is similar to reported earlier for smaller particles [23]. The flow in the channel is symmetric, leading to focusing of particles at two symmetric equilibrium positions.…”
Section: Resultssupporting
confidence: 85%
“…However, the particle velocity in the channel can differ significantly from that of a fluid due to hydrodynamic interactions with the walls. It has recently been suggested that in a symmetric no-slip hydrophilic channel this difference can be characterized by the correction functions h ξ and h η [23]:…”
Section: Model and Theoretical Estimatesmentioning
confidence: 99%
“…Observe that the inertial lift force on the particle gets stronger as the particle nears the bottom wall and this acts as a re-suspension mechanism to elevate the particle a little from the bottom wall. This is also observed in much simpler studies of the combined effects of gravity and inertial lift force on a spherical particle suspended in flow between two plane parallel walls (Asmolov et al 2018). Further, although to a lesser extent, the secondary component of the background flows acts to pull the particle up from the bottom wall in the half of the duct adjacent to the inside wall (relative to the centre of the duct bend).…”
Section: Significant Changes In Focusing When Fr 2 = O(1)mentioning
confidence: 65%
“…This interesting lateral particle migration was also known as the "tubular pinch effect." After the first discovery of this phenomenon in the 1960s, a number of theoretical studies (Saffman 1965;Cox and Brenner 1968;Ho and Leal 1974;Schonberg and Hinch 1989;Asmolov 1999;Matas et al 2004;Asmolov et al 2018) have been carried out to uncover its underlying physics. Up until now, the most well-accepted explanation is that this lateral particle migration is caused by the inertial lift force (F L ) which is actually the resultant of the shear-gradient-induced inertial lift force (F LS ) and the wall-induced inertial lift force (F LW ) (Di Carlo et al 2007).…”
Section: Inertial Migrationmentioning
confidence: 99%